Comparative proteome and metabolome analyses of latex-exuding and non-exuding Taraxacum koksaghyz roots provide insights into laticifer biology. (19th November 2019) - Benninghaus, Vincent Alexander; van Deenen, Nicole; Müller, Boje; Roelfs, Kai-Uwe; Lassowskat, Ines; Finkemeier, Iris; Prüfer, Dirk; Schulze Gronover, Christian
Abstract : Using a toxin/anti-toxin system, comprehensive proteome and metabolome analyses of roots of transgenic Taraxacum koksaghyz plants with or without latex exudation provide insights into latex-specific protein isoforms and metabolic pathways. Abstract: Taraxacum koksaghyz has been identified as one of the most promising alternative rubber crops. Its high-quality rubber is produced in the latex of laticifers, a specialized cell type that is organized in a network of elongated tubules throughout the entire plant body. In order to gain insights into the physiological role(s) of latex and hence laticifer biology, we examine the effects of barnase-induced latex RNA degradation on the metabolite and protein compositions in the roots. We established high-quality datasets that enabled precise discrimination between cellular and physiological processes in laticifers and non-laticifer cell types of roots at different vegetative stages. We identified numerous latex-specific proteins, including a perilipin-like protein that has not been studied in plants yet. The barnase-expressing plants revealed a phenotype that did not exude latex, which may provide a valuable genetic basis for future studies of plant–environment interactions concerning latex and also help to clarify the evolution and arbitrary distribution of latex throughout the plant kingdom. The overview of temporal changes in composition and protein abundance provided by our data opens the way for a deeper understanding of the molecular interactions, reactions, and network relationships that underlie the different metabolic pathways in the roots of this potential rubber crop.